RENAL INFUNDIBULAR STENOSIS WITH UROLITHIASIS: A LITERATURE REVIEW - Firmanto, Rama; Rasyid, Nur (Indonesian Urological Association, 2020)
Objective: This literature review was performed to improve the insight in renal infundibular stenosis with urolithiasis. Material & Methods: We searched several literatures about infundibular stenosis and its association with urolithiasis. Pubmed and ScienceDirect databases were used to identify relevant studies. Results: Infundibulopelvic stenosis (IFPS) is rarely found. It is not always a congenital condition. IFPS is caused by extrinsic factor, such as carcinoma or retroperitoneal fibrosis, or intrinsic factor, such as inflammation, infection, calculus, Fraley’s syndrome, or surgery performed on kidney. Urinary stasis in the pelvicalyceal system that happened in IFPS increases the chance of stone formation. Its anatomical abnormality plays important role to stone formation. The clear treatment algorithm has not been found. The management for kidney stones depends on stone characteristic, location, and symptoms of the patient, as recommended by Koopman et al. Bayne et al. recommend methods of nephrotomy and calicocalicostomy. While Balbo et al. recommend holmium-based therapy. Conclusion: Infundibulopelvic stenosis is a risk factor of urolithiasis. It is a rare condition, but the treatment algorithm has not been found. There are several recommendations for kidney stone management in infundibulopelvic stenosis.